KARAKTERISTIK ENDAPAN BIJIH BESI LATERIT PADA BLOK BARAT DAN BLOK TIMUR PT SILO, KABUPATEN KOTABARU, KALIMANTAN SELATAN BERDASARKAN ANALISIS GEOKIMIA DAN MINERALOGI : CHARACTERISTICS OF LATERITE IRON ORE DEPOSIT IN WEST BLOCK AND EAST BLOCK OF PT SILO, KOTABARU DISTRICT, SOUTH KALIMANTAN BASED ON GEOCHEMICAL AND MINERALOGICAL ANALYSIS - Putri Ramadhani, Ayumi Hana; Andi Cahyadi; Tatik Handayani; Suwahyadi (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2023)
This research was conducted to identify the characteristics of laterite deposits in the western and eastern blocks of Sebuku Island, Kotabaru Regency, South Kalimantan using field observation methods, and laboratory analysis including titration, XRF, XRD and petrography analysis. The characteristics of the western block laterite deposits are 10 meters until 15 meters deep. The red limonite zone has Fe content of 51.25% with a mineral composition of hematite, magnetite, goethite, ilmenite, spinel. The yellow limonite zone has Fe content of 50.1% with a mineral composition of goethite, hematite, gibsite, ilmenite. The saprolite zone has Fe content of 16.2%, the mineral composition is hematite, chrysotile, goethite, garnet, diopside. The characteristics of the eastern block laterite deposits are that they have a depth of 6 meters until 7.5 meters. The red limonite zone has Fe content of 47.38% with a mineral composition of hematite, goethite, ilmenite, spinel. The yellow limonite zone has Fe content of 38.70% with a mineral composition of goethite, hematite, chromite, gibbsite, spinel. The saprolite zone has Fe content of 15.08%, the mineral composition is hematite, goethite, diopside, fayalite. The bedrock of the research area is in the form of periodotite, namely dunite and harzburgite which have been serpentinized. The mineral composition of the bedrock is olivine, pyroxene, opaque minerals and several secondary minerals, namely serpentine and talc. The west block bedrock has Fe content of around 7.73 % until 8.03% while the east block bedrock has Fe content of around 6.59 % until 7.49%.